Cultural Heritage Folk Crafts Management: Contribution to the Welfare and Stability of Local Wisdom - Aini, Desti Nur; Winarno, Agung (Technium Social Sciences Journal, 2022)
The purpose of this study is to reveal the management of the variety and quality of pottery products as a cultural heritage that contributes to the welfare of craftsmen and the community as well as the stability of local wisdom. Continuity and changes are made by the craftsmen as a result of the flood of products with the same function made of manufactured plastic. This study employed a Participatory Rural Appraisal (PRA) approach, which used approaches and policies in Pagelaran Village, Malang Regency by involving the community as effectively as possible. The data mining technique is in the form of participatory mapping. The results showed that, to improve the welfare of craftsmen, they carried out a harmonious combination of adaptive behavior and adaptive strategies that were carried out explicitly or implicitly in response to various environmental conditions in order to promote the variety and quality of local traditional pottery products. The community implicitly carries out the process of adjusting the cultural heritage of pottery by maintaining the sustainability and continuity of local traditional pottery products. Meanwhile, the development of a variety of products is explicitly carried out which leads to a shift in the function of the pottery itself as an effect of socio-cultural changes.